FINTECH DALAM PEMBERDAYAAN USAHA PEREMPUAN: MEMPERKUAT IMPLEMENTASI GREEN INNOVATION DAN GREEN ACCOUNTING UNTUK KEBERLANJUTAN BISNIS - Fitriana, Aning; Tyas, Karunia Zuraidaning; Wahyuningsih, Esti (Ultimaccounting Jurnal Ilmu Akuntansi, 2025)
Abstract— Limited digital financial knowledge, restricted access to technology, and low adoption of Green Accounting and Green Innovation practices remain significant obstacles to the sustainable success of female entrepreneurs. Limited access to external funding further complicates the adoption of environmentally friendly business practices in rural areas. This research focuses on how Fintech helps enhance the adoption of Green Innovation and Green Accounting, thereby improving business sustainability for women-owned micro, small, and medium enterprises (MSMEs). The distinctiveness of this research lies in its positioning of Fintech as an essential enabler of women's economic empowerment. It also presents a comprehensive framework that links digital financial services with sustainable management practices, an area that has yet to be thoroughly investigated. Data was gathered through a quantitative research method from a survey involving 100 female entrepreneurs in the historical Banyumas area. The data were examined through Structural Equation Modeling (SEM) utilizing SmartPLS. The study indicates that both Green Innovation and Green Accounting significantly contribute to promoting corporate sustainability. Moreover, although Fintech does not influence the effect of Green Innovation, it does influence the relationship between Green Accounting and sustainability. This study contributes to the existing literature on sustainability by integrating perspectives on sustainability, eco-friendly practices, and digital finance within a framework focused on gender in micro, small, and medium enterprises (MSMEs). The results emphasize the importance of focusing on digital financial literacy, developing Fintech-driven environmental reporting, and establishing capacity-building initiatives to encourage sustainable business practices among women entrepreneurs. Keywords: Fintech; Women; Green Innovation; Green Accounting; Business Sustainability